2012
DOI: 10.1136/bmj.e5888
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intervention on physical activity of children: systematic review and meta-analysis of controlled trials with objectively measured outcomes (EarlyBird 54)

Abstract: Objective To determine whether, and to what extent, physical activity interventions affect the overall activity levels of children.Design Systematic review and meta-analysis.Data sources Electronic databases (Embase, Medline, PsycINFO, SPORTDiscus) and reference lists of included studies and of relevant review articles.Study selection Design: randomised controlled trials or controlled clinical trials (cluster and individual) published in peer reviewed journals. Intervention: incorporated a component designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
489
5
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(538 citation statements)
references
References 74 publications
33
489
5
11
Order By: Relevance
“…Unfortunately, these interventions have minimally impacted the body weight and total PA of children, likely because the amount of PA prescribed was insufficient. 2 Interventions that substantially impact the amount of PA children accumulate could have a more meaningful impact on their body weight, as observed in adults. 3,4 Children accumulate their PA by engaging in active play (also referred to as physically active play, PA play, and active free play) and organized PA such as organized sport, active transportation, and physical education and other organized school activities.…”
mentioning
confidence: 99%
“…Unfortunately, these interventions have minimally impacted the body weight and total PA of children, likely because the amount of PA prescribed was insufficient. 2 Interventions that substantially impact the amount of PA children accumulate could have a more meaningful impact on their body weight, as observed in adults. 3,4 Children accumulate their PA by engaging in active play (also referred to as physically active play, PA play, and active free play) and organized PA such as organized sport, active transportation, and physical education and other organized school activities.…”
mentioning
confidence: 99%
“…In a recent systematic review, Metcalf, Henley and Wilkin carried out a meta‐analysis of interventions to increase physical activity in children and concluded that such interventions had only a small effect (about four minutes more walking or running per day) on children's overall activity levels 6 . Clearly, our present systems are failing and have been doing so for some time 6 . Successive generations of Australian school children have lost their free play and other opportunities to be active have been eroded from daily life 41 .…”
Section: Resultsmentioning
confidence: 99%
“…We also consider recent systematic reviews and meta‐analyses 4 , 5 , 6 , 7 summarising research efforts – to date, largely unsuccessful – to prevent or reverse obesity in children, and offer some insights into why failure to achieve clinically significant impact is so prevalent and what policies or strategies might increase the chances of success.…”
mentioning
confidence: 99%
“…Unfortunately, however, the accumulated evidence to date suggests that the effectiveness of these interventions have been limited. To illustrate, in a recent meta-analysis that examined the effects of interventions that were tested using controlled trials in relation to objective measures of physical activity among children, the overall effect of the interventions was very small and equated to an average increase of just 4 min more of walking or running per day on children's overall activity levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, however, the accumulated evidence to date suggests that the effectiveness of these interventions have been limited. To illustrate, in a recent meta-analysis that examined the effects of interventions that were tested using controlled trials in relation to objective measures of physical activity among children, the overall effect of the interventions was very small and equated to an average increase of just 4 min more of walking or running per day on children's overall activity levels [4].Given the current evidence regarding (a) the small effects that the best pediatric physical activity interventions can deliver, (b) the pervasive levels of inactivity that exist among children, and (c) the considerable health-related and developmental costs associated with inactivity among this population, we propose that it is time for a substantive rethink about our …”
mentioning
confidence: 99%